Forage development Pennisetum purpureum (Schumach) cv. BRS Kurumi on application Azospirillum brasiliense (N), Bacillus subtilis (P) - Rodrigues, Diego Alves (2022)
Experiment conducted at Fazenda Sem Fronteiras in the municipality of Xinguara in the state of Pará, using the forage Pennisetum purpureum (Schumach) cv. BRS Kurumi, with the objective of evaluating the feasibility of using the nitrogen inoculating bacteria Azospirillum brasiliense and phosphorous Bacillus subtilis in the development, as well as the vegetative propagation through the height and appearance of tillers, production of natural matter (mn), dry matter (DM) ) and carrying capacity in UA/ha. The plants were arranged in treatments of 16m² with 16 plants each treatment. The first treatment (T1) used inoculation with A. brasilense and Bacillus s. plus fertilization, the second treatment (T2) was only fertilized. (T1) and (T2) were fertilized with nitrogen source 20 days after planting, third treatment (T3) control. The height was measured and the appearance of tillers of the plants was counted in a period of 60 days of experiment with an interval of 15 days, submitted to the ANOVA test at the level of (p<0.05). No significance was observed for height in the different treatments, however, for counting the number of tillers, significance was observed after the second reading. At the end of the experiment, a sample of natural matter (mn) was collected to determine the production in tons/ha, DM, and carrying capacity in AU/ha. Monthly average (kg/ha) T1=1110; T2=1000; T3=900. Annual average (kg/ha/year). T1=135,670; T2=119.401; T3=100.460. %MS, T1=21%; T2=19% T3=19%. AU/ha, T1=8.2; T2=7.2; T3=6.5.